M6A mRNA methylation in human brain is disrupted in Lewy body disorders. Issue 1 (27th February 2023) - Martinez De La Cruz, Braulio; Gell, Chris; Markus, Robert; Macdonald, Ian; Fray, Rupert; Knight, Helen Miranda
Abstract: Aims: N 6 ‐methyladenosine modification of RNA (m 6 A) regulates translational control, which may influence neuronal dysfunction underlying neurodegenerative diseases. Methods: Using microscopy and a machine learning approach, we performed cellular profiling of m 6 A‐RNA abundance and YTHDF1/YTHDF3 m 6 A reader expression within four regions of the human brain from non‐affected individuals and individuals with Parkinson's disease, dementia with Lewy bodies or mild cognitive impairment (MCI). Results: In non‐diseased tissue, we found that m 6 A‐modified RNAs showed cell‐type and sub‐compartment‐specific variation. YTHDF1 and YTHDF3 showed opposing expression patterns in the cerebellum and the frontal and cingulate cortices. Machine learning quantitative image analysis revealed that m 6 A‐modified transcripts were significantly altered in localisation and abundance in disease tissue with significant decreases in m 6 A‐RNAs in Parkinson's disease, and significant increases in m 6 A‐RNA abundance in dementia with Lewy bodies. MCI tissue showed variability across regions but similar to DLB; in brain areas with an overall significant increase in m 6 A‐RNAs, modified RNAs within dendritic processes were reduced. Using mass spectrometry proteomic datasets to corroborate our findings, we found significant changes in YTHDF3 and m 6 A anti‐reader protein abundance in Alzheimer's disease (AD) and asymptomatic AD/MCI tissue and correlation with cognitive resilience. Conclusions: These results provide evidence for disrupted m 6 A regulation in Lewy body diseases and a plausible mechanism through which RNA processing could contribute to the formation of Lewy bodies and other dementia‐associated pathological aggregates. The findings suggest that manipulation of epitranscriptomic processes influencing translational control may lead to new therapeutic approaches for neurodegenerative diseases. Abstract : Using microscopy and a machine learning approach, we performed subcellular profiling of m 6 A‐RNA abundance in human brain from non‐affected individuals and individuals with neurodegenerative diseases. m 6 A‐RNAs were found consistently more abundant in dementia with Lewy bodies tissue and significantly reduced or misplaced in brain tissue from individuals with Parkinson's disease. The findings of disrupted m 6 A‐RNAs in Lewy body diseases are consistent with evidence for alterations in the control of RNA translation contributing to the formation of protein aggregate neurotoxic structures.